Aktualisasi Sad Kertih Sebagai Dasar Tatanan Kehidupan - Agus Aditya Saputra; Ni Putu Ayu Heppyana (Pramana: Jurnal Hasil Penelitian, 2023)
The development process that will be carried out actually functions to maintain the sustainability, existence and cleanliness of the environment. Human life as an individual who is a social creature in his life is always side by side with one another. The ecological crisis is increasing in every process of life. This crisis becomes a complex problem for people's lives if it is not handled properly. In order to realize a harmonious life in the modern era with the preservation of the existence of the universe, basic principles are needed as guidelines for Hindus to actualize in their lives by understanding the teachings of Sad Kertih, one of its parts and applying them in everyday life. it is stated that Sad Kerti's writing is separated so that the word has the meaning of six noble behaviors that are embodied in building the order of Balinese life. However, if the writings of SadKerti become one, then the word Sad is actually Sat which means truth and kert which means noble behavior. Within the six concepts referred to in Sad Kerti there are Atma Kertih, Samudra Kertih, Wana Kertih, Danu Kertih, Jagat Kertih, and Jana Kertih. With Sad Kertih's teachings the goal is actualized as the basis of the order of life, besides that with the presence of Nangun Sat Kerti's vision Loka Bali further strengthens the values of Sad Kertih's teachings because in that vision the values of Sad Kertih's teachings are also outlined so that the Hindu community is increasingly convinced that Sad Kertih is a religious teaching that should be used as a basis in the order of life.